NERACA AIR DI PDAM LAWU TIRTA KABUPATEN MAGETAN - Indah Nofitasari; Sunaryo, Sunaryo; Beny Suyanto; Hery Koesmantoro; Wiyono, Wiyono (Nusantara Hasana Journal, 2024)
The Lawu Tirta Magetan Regional Drinking Water Company (PDAM) needs to conduct a water balance study, this is due to the increasing demand for water for the community which is getting bigger, while the existing water debit is limited. This research aims to determine the level of water demand needed by the community until 2032 This type of research is descriptive, by collecting secondary and primary data where the primary data includes projected population and the need for clean water for the community, then the data that has been collected will be explained and analyzed to provide an overview of the water balance in current conditions for the next 10 years. The service area of PDAM Lawu Tirta serves 76.377 customers located in 18 sub-districts covering 330 villages with a sample of 3 large sub-districts and 3 small sub-districts in 25 villages with a total sample of 400 connections. The research findings indicate that from the clean water demand survey in larger/urban sub-districts, the average is 495 liters (L/O/H), while in smaller/rural districts, it is 199 L/O/H. As a result, the average clean water demand for the Magetan community is 346 L/O/H. The clean water requirement for the year 2023 is projected to be 894,08 liters per second, with the current available discharge at 813.34 liters per second. For the year 2032, the projected water demand is 1.045,28 liters per second. Therefore, the available water discharge is not sufficient to meet consumer needs until the year 2032. To address this issue, necessary steps include adding deep wells, constructing reservoirs, establishing water treatment plants (IPA), and creating infiltration wells in spring areas. The current water discharge owned by PDAM Lawu Tirta is 813,34 liters per second. Alongside the population growth and the subsequent increase in water demand, the existing water discharge is inadequate until the year 2032. For this study it is necessary to carry out further research on water needs with a larger sample in order to obtain more perfect results, it is necessary to survey the percentage of the population that has not been served by PDAM water in the next 10 years with growth rates, it is necessary to examine the development of non-domestic networks.